An investigation into using american movies in moitivating 11th form English gifted students at Lam Son gifted high school-Thanh Hoa province to understand american culture = Nghiên cứu cách sử dụng phim Mỹ trong dạy tiếng Anh nhằm tạo động lực tìm hiểu v - Nguyễn, Thị Phương (University of Languages and International Studies, 2017)
The importance of American culture is undeniable in English language. Therefore, investigating new ways to motivate students to learn American culture is apparently necessary to gain effective English teaching and learning and using American movies in the process is not exception. This minor thesis was carriedout with an investigation into using American movies in motivating 11th form English gifted students at Lam Son Gifted High School -Thanh Hoa province to understand American culture. The minor thesis is organized in 3 parts:Part A:presents the rationale, aims and significance of the study, research questions, scope, method and design of the study.Part B:consists of 4 chapters The first chapter concentrates on the background of the study and the related literature reviews, on which the contents of the study are based. The second chapter focuses on developing the research methodology, in which the two questionnaires for 11thform English gifted students and teachers of English at Lam Son Gifted High School are chosen as main instruments. The third chapter is to present the data collected from the two questionnaires and to analyze the data. The fourth chapter aims at discussing the findings on how to use American movies in English class as the best solutions in the hope to motivate 11thform English gifted students to understand American culture